2013
DOI: 10.1128/jb.02151-12
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae VttR A and VttR B Regulatory Influences Extend beyond the Type 3 Secretion System Genomic Island

Abstract: A subset of non-O1/non-O139 serogroup strains of Vibrio cholerae cause disease using type 3 secretion system (T3SS)-mediated mechanisms. An ϳ50-kb genomic island carries genes encoding the T3SS structural apparatus, effector proteins, and two transmembrane transcriptional regulators, VttR A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…Previous results from our laboratory showed that VttR A and VttR B modulate T3SS island gene expression in vitro in the presence of bile (31,34). Data also support a model for hierarchical regulation whereby VttR A regulates the expression of vttR B , since both a ⌬vttR A single-deletion strain and a ⌬vttR A ⌬vttR B double-deletion strain can be complemented for T3SS gene expression by providing vttR B in trans (32).…”
Section: Resultssupporting
confidence: 61%
“…Previous results from our laboratory showed that VttR A and VttR B modulate T3SS island gene expression in vitro in the presence of bile (31,34). Data also support a model for hierarchical regulation whereby VttR A regulates the expression of vttR B , since both a ⌬vttR A single-deletion strain and a ⌬vttR A ⌬vttR B double-deletion strain can be complemented for T3SS gene expression by providing vttR B in trans (32).…”
Section: Resultssupporting
confidence: 61%
“…Recently genetic, biochemical, and transcriptome analyses have been used to reveal the role of bile salts in inducing the pathogenesis of different enteric bacteria (Joyce & Gahan, ; Sistrunk et al, ). Bile salts mediate reciprocal host‐pathogen crosstalk (Chaand & Dziejman, ; Gotoh et al, ), and there is increasing evidence supporting the role of bile salts in regulating bacterial virulence gene expression (Li et al, ; Xue et al, ; Yang et al, ). ST plays an important role in inducing V .…”
Section: Discussionmentioning
confidence: 99%
“…Although functions of VPA1351 and VPA1353 are not yet determined, VPA1351 is predicted to have structural homology with an MS ring protein of Salmonella enterica SPI‐1 T3SS . In addition, V. cholerae VopH and VopA are required for T3SS effector translocation by the V. cholerae strain AM‐19226 . Based on these observations, VPA1351 and VPA1353 are probably T3SS2‐apparatus‐related proteins, rather than functional effectors in host cells.…”
Section: T3ss2 Effectors: Repertoire and Mechanisms Of Actionmentioning
confidence: 99%